Language Learning Strategies for Managing Speaking Anxiety among English Students: A Narrative Inquiry - Santiana Santiana; Ningsih Yulianti; Sitti Syakira; Tariq Khan; Supaprawat Siripipathanakul (Universitas Islam Negeri Madura, 2026)
Speaking anxiety is one of the most prominent obstacles for EFL students in improving their speaking skills. Successful students use more language learning strategies to overcome their speaking anxiety. This study aims to portray the experiences of an English education department student in dealing with speaking anxiety. More specifically, this study focuses on studentâ€™s speaking anxiety experience and the utilisation of language learning strategies. To achieve the objective of the study, a narrative inquiry is employed. The data collection methods are semi-structured interviews and photo elicitation. The interview data was translated into English, re-examined, and analysed using narrative analysis (Labov, 1972). The findings of this study indicate that a student experience speaking anxiety due to several factors, and utilising language learning strategies helped in reducing speaking anxiety itself. The findings of this study are presented in the narrative analysis framework proposed by Labov (1972): (1) Abstract: â€œThe Early Motivationâ€, (2) Orientation: â€œA Supportive Environment as the Starting Lineâ€, (3) Complicating action: â€œFacing Fear in English Speakingâ€, (4) Resolution: â€œStrategy Adoption as Emotional Regulationâ€, (5) Evaluation: â€œFrom Avoidance to Agencyâ€, (6) Coda: â€œRediscovering Joy in Speakingâ€. This study suggests applying language learning strategies as it can assist students in coping with speaking anxiety.